2021
DOI: 10.1017/s1744137421000059
|View full text |Cite
|
Sign up to set email alerts
|

Financial constraint, trust, and export performances: firm-level evidence from Africa

Abstract: Several existing studies have documented a negative relationship between firm financial constraint and export activities but do not attempt to examine factors that could attenuate this relationship in Africa. In this paper, we examine the effect of financial constraint on exports in Africa and explore how the level of trust in countries where firms are located shapes this relationship. We combine the World Bank Enterprise Surveys with different measures of country-level personal and interpersonal trust compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…In finance development, the effect of trust is also explored. Overall, a large number of works support that trust is beneficial to financial development (Pevzner et al, 2015;Guiso et al, 2004;Konte & Ndubuisi, 2021).…”
Section: 1why Should Trust Affect Economic Performance?mentioning
confidence: 99%
See 2 more Smart Citations
“…In finance development, the effect of trust is also explored. Overall, a large number of works support that trust is beneficial to financial development (Pevzner et al, 2015;Guiso et al, 2004;Konte & Ndubuisi, 2021).…”
Section: 1why Should Trust Affect Economic Performance?mentioning
confidence: 99%
“…The nexus between social capital measured by trust and socio-economic conditions has been widely explored (Pevzner et al, 2015;Guiso et al, 2004;Konte & Ndubuisi, 2021;D'Hombres et al, 2009 ;Herian et al, 2014;Carpiano & Fitterer, 2014;Hollard & Sene, 2016). Similarly, a large body of studies in the literature has examined the effects of diversity on several economic outcomes (Easterly & Levine, 1997;Collier, 2001;Alesina et al, 2003;Alesina & La Ferrara, 2005;Montalvo & Reynal-Querol, 2005;Ager & Brückner, 2013;Gisselquist et al, 2016;Wei & Suen, 2019;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial constraint also deteriorates firms' investment and lack of such investment in exporting means limits competition and negative affects export performance (Kazmi et al, 2020). The financial constraint also negatively affects export performance because due to the sunk cost involved in exporting and the time lag between exporting and receiving revenue, many SMEs turn to limit their operations which makes them less competitive in foreign markets (Saeed and Vincent, 2011;Konte and Ndubuisi, 2021;Máñez and Vicente-Chirivella, 2021). This negative relationship between export barrier on export performance is evident in existing literature (e.g., Sinkovics et al, 2018;Suarez-Ortega 2003;Altintas et al, 2007;Leonidou 2004;Tesfom et al, 2006).…”
Section: Export Barriers and Export Performancementioning
confidence: 99%
“…Access to finance is vital for the survival of SMEs during the pandemic crisis. Several studies have shown that SMEs are financially more constrained than large firms (Beck & Demirguc‐Kunt, 2006 ; Konte & Ndubuisi, 2021 ; Kuntchev et al, 2012 ), and the presence of financial constraints exerts a negative impact on the growth and survival of SMEs (Oliveira & Fortunato, 2006 ). For example, one study estimates that the presence of financial constraints is associated with a 10 percentage point reduction in the growth of small firms (Beck et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%